Social Innovation for Agricultural Development: A Study of System of Rice Intensification in Bihar, India. (April 2020) - Kumar, Vikas
The social innovation inclines to an emphasis on 'systems and processes of change in social relations' and 'innovation is a new idea, product or process that addresses social and environmental challenges and their needs'. It is newly growing up as a field of practice that is done by people. It has occurred from the broader field of innovation studies. In this article, the System of Rice Intensification (SRI) has been taken as a case of social innovation, which helps to increase the productivity of rice and enhance the income of the farmers. The literature related to SRI suggested that the technique is sustainable and innovative because of the less use of inputs and changes in some set of principles (i.e., planting, fertilizer, water and seeds) whereas increasing output in terms of production and productivity of the crop. In this sense, aim of the article is to evaluate the impact of the SRI technique within the framework of social innovation in Patna district, Bihar, India. In a wider context, the question is not about whether it is intensifying or not, rather emphasis should be on how farmers deal with changing environmental and socio-economic factors. Moreover, there is a need to delve deeper into implantation strategies in the local context and evaluate their impact in terms of opportunities and constraints during adaptation. In addition to this, an exploratory research design was followed to study SRI. Criterion and expert sampling were employed to select the farmers, and data were collected by a personal interview method with the help of a structured schedule. However, the data indicate the production and productivity of paddy are increased through SRI, but variation exists among different blocks of the district. It is clearly evident from the data that nearly 42 per cent of farmers from all blocks have witnessed an increase in food sufficiency. In the case of income due to the sale of excess produce is 57 per cent.